Effect of Al addition in HfO2 on the optical properties of the dielectrics using spectroscopy ellipsometry. (31st March 2015) - Fan, Xiaojiao; Liu, Hongxia; Zhong, Bo; Fei, Chenxi; Wang, Xing; Wang, Qianqiong
Abstract: The imaginary part of the dielectric functions ( ϵ 2 ) and the band gap energy ( E g ) of Al-HfO2 films with different Al incorporation levels prepared by atomic layer deposition (ALD) are extracted using variable angle spectroscopic ellipsometry (VASE). The analysis results show that pure HfO2 film exhibits crystallization features after annealing at 500 °C. When Al is incorporated, Al-HfO2 films can maintain amorphous at temperatures up to 700 °C after rapid thermal annealing, indicating a good thermal stability. In particular, as-deposition [1Al2 O3 + 5HfO2 ] film shows similar optical properties to that of pure HfO2 . Moreover, least disorder in the amorphous film structure and excellent thermal stability of E g (5.5 ± 0.1 eV) during annealing are obtained for [1Al2 O3 ± 5HfO2 ] films. However, increased Al incorporation levels induce more disorder in the amorphous film structure and thermal instability of E g during the annealing procedure. Thus, [1Al2 O3 ± 5HfO2 ] film displays the optimal optical properties and excellent thermal stability of E g .